Intranasal Microemulsion as an Innovative and Promising Alternative to the Oral Route in Improving Stiripentol Brain Targeting - Meirinho, Sara (2023)
Stiripentol (STP) is a new-generation antiepileptic only available for oral administration. However, it is extremely unstable in acidic environments and undergoes gastrointestinal slow and incomplete dissolution. Thus, STP intranasal (IN) administration might overcome the high oral doses required to achieve therapeutic concentrations. An IN microemulsion and two variations were herein developed: the first contained a simpler external phase (FS6); the second one 0.25% of chitosan (FS6 + 0.25%CH); and the last 0.25% chitosan plus 1% albumin (FS6 + 0.25%CH + 1%BSA). STP pharmacokinetic profiles in mice were compared after IN (12.5 mg/kg), intravenous (12.5 mg/kg), and oral (100 mg/kg) administrations. All microemulsions homogeneously formed droplets with mean sizes ≤16 nm and pH between 5.5 and 6.2. Compared with oral route, IN FS6 resulted in a 37.4-fold and 110.6-fold increase of STP plasmatic and brain maximum concentrations, respectively. Eight hours after FS6 + 0.25%CH + 1%BSA administration, a second STP brain concentration peak was observed with STP targeting efficiency being 116.9% and direct-transport percentage 14.5%, suggesting that albumin may potentiate a direct STP brain transport. The relative systemic bioavailability was 947% (FS6), 893% (FS6 + 0.25%CH), and 1054% (FS6 + 0.25%CH + 1%BSA). Overall, STP IN administration using the developed microemulsions and significantly lower doses than those orally administrated might be a promising alternative to be clinically tested.